Women on ice: methamphetamine use among suburban women - Boeri, Miriam (Critical issues in crime and society, 2013)
Methamphetamine : the perfect drug for suburban women -- Ethnographic research : exploring methamphetamine use in the suburbs -- The gendered drug career : initiation and progression in methamphetamine use -- Gendered lives : combining work and family with drug-using roles -- Gendered risks : health and infectious diseases -- Gendered risks : violence and crime -- The revolving door : treatment, recovery, and relapse -- Policy implications